2018
DOI: 10.3389/fimmu.2018.00767
|View full text |Cite
|
Sign up to set email alerts
|

Resetting the T Cell Compartment in Autoimmune Diseases With Autologous Hematopoietic Stem Cell Transplantation: An Update

Abstract: Autologous hematopoietic stem cell transplantation (aHSCT) for autoimmune diseases has been applied for two decades as a treatment for refractory patients with progressive disease. The rationale behind aHSCT is that high-dose immunosuppression eliminates autoreactive T and B cells, thereby resetting the immune system. Post-aHSCT the cytotoxic CD8+ T cells normalize via clonal expansion due to homeostatic proliferation within a few months. CD4+ T cells recover primarily via thymopoiesis resulting in complete re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
2
12
0
2
Order By: Relevance
“…aHSCT is a well-established treatment for hematologic malignancies and is increasingly used for refractory autoimmune diseases to halt autoimmune destruction and reestablish tolerance ( 10 ). The putative mechanism points to greater diversity in the T-cell repertoire ( 11 ), thymus reactivation of regulatory T cells (Tregs) ( 12 ), and an increase in the function or number of Tregs ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…aHSCT is a well-established treatment for hematologic malignancies and is increasingly used for refractory autoimmune diseases to halt autoimmune destruction and reestablish tolerance ( 10 ). The putative mechanism points to greater diversity in the T-cell repertoire ( 11 ), thymus reactivation of regulatory T cells (Tregs) ( 12 ), and an increase in the function or number of Tregs ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, NTZ increased TCR expansion in PB (18). AHSCT, in turn, was found to result in a complete renewal of CD4+ T cells along with the persistence of selected CD8+ clones (11,12).…”
Section: Introductionmentioning
confidence: 85%
“…In MS patients, the TCR repertoire was investigated in blood, cerebrospinal fluid, and lesions (11,12). They found that CD4+ and CD8+ cells are expanded in CNS perivascular spaces and in MS lesions, respectively (13), and that Epstein-Barr virus (EBV)reactive clones are compartmentalized and expanded in MS brain (14).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these premises, the use of HSCs has been tested in numerous autoimmune diseases such as type 1 diabetes (T1D), multiple sclerosis (MS), systemic sclerosis, systemic lupus erythematosus and Chron's disease, with relevant benefits (3)(4)(5)(6). Indeed, HSCs may reset the immune response, thus reshaping the chronic derangement of the immune system to a more selftolerant state (7,8). Interestingly, it has been also demonstrated that the bone marrow-derived and blood HSCs are altered in some autoimmune conditions such as T1D and MS, with HSCs being scanty in the circulation and often unable to exploit their immunoregulatory function (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%